2003
DOI: 10.2337/diacare.26.3.744
|View full text |Cite
|
Sign up to set email alerts
|

Unadjusted and Adjusted Prevalence of Diagnosed Depression in Type 2 Diabetes

Abstract: OBJECTIVE -To estimate the prevalence of diagnosed depression in a large population of individuals with type 2 diabetes, compared to a matched control group, and to estimate the extent of depression that is independently associated with diabetes. RESEARCH DESIGN AND METHODS-We compared the prevalence of diagnosed depression in all 16,180 full-year health maintenance organization members in 1999 who had been diagnosed with type 2 diabetes and in 16,180 comparison members without diabetes matched for age and sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
79
3
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(100 citation statements)
references
References 29 publications
13
79
3
5
Order By: Relevance
“…4 Our finding is also in line with those earlier ones that have shown an association between depression and type II diabetes. 1,17 We consider, however, our finding important, as in the present study, the association between IR and depressive symptoms was confirmed in young adult males, in which earlier diagnosed diabetes was excluded. Further investigations are, however, called for to confirm our results, as according to a recent prospective cohort study, no association was found between IR and depressive symptoms in middle-aged men.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…4 Our finding is also in line with those earlier ones that have shown an association between depression and type II diabetes. 1,17 We consider, however, our finding important, as in the present study, the association between IR and depressive symptoms was confirmed in young adult males, in which earlier diagnosed diabetes was excluded. Further investigations are, however, called for to confirm our results, as according to a recent prospective cohort study, no association was found between IR and depressive symptoms in middle-aged men.…”
Section: Discussioncontrasting
confidence: 41%
“…Recently, Rasgon et al 19 found that in a clinical sample of women with polycystic ovary syndrome, which is characterized by hyperandrogenism and IR, 50% of the patients were considered depressed. Further, while confirming an independent association between depression and type II diabetes, a large population-based investigation 17 suggested also that the relationship between depression and IR-related conditions (like type II diabetes, cardiovascular disease and obesity) differed between men and women. Therefore, further investigations regarding the impact of gender on the association between IR and depression are needed.…”
Section: Discussionmentioning
confidence: 82%
“…It remains unclear how depressive symptoms affect coronary heart disease and other complications, although several explanations have been put forward. Depression is linked to type 2 diabetes (18,19), hypertension (20), and low high-density lipoprotein-cholesterol (21), all of which are major risk factors for coronary heart disease. Moreover, a patient with depression tends to have poorer health behavior, e.g., they are less active (22).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between type 2 diabetes and major depression has long been observed and extensively studied (Leonard et al, 2002;Anderson et al, 2001;Nichols et al, 2003). Individuals with diabetes were twice as likely as a comparable sample to be diagnosed with comorbid depression (estimated at around 15% to 20% in patients with diabetes).…”
Section: Introductionmentioning
confidence: 99%